Vigor assessment of juvenile rubber tree clones in Northwestern São Paulo State, Brazil - Piffer Gonçalves, Elaine Cristine; Lima Gouvêa, Lígia Regina; Mello Martins, Antonio Lúcio; Botelho Ferraz Branco, Roberto; de Souza Gonçalves, Paulo (Revista Ceres, 2025)
Besides rubber production, one of the main goals of the genetic improvement of rubber tree [Hevea brasiliensis (Willd. ex Adr. de Juss.) Muell. Arg.] is to develop vigorous clones. The objective of the present study was to evaluate the vigor of 34 elite juvenile rubber clones. To this end, three experiments were conducted in the municipality of Pontes Gestal, in the northwest region of the São Paulo State. Each experiment consisted of 10 treatments, and 2 controls in common to the 3 experiments. The experiments were arranged in the randomized block design, with three replications and ten plants per plot, in the 8 m x 2.5 m spacing. Individual and joint analyses of variance were performed. The means were compared using the Dunnett test at 5%. Significant effect of treatments was found in the three experiments and in the joint analysis. The most vigorous clones were not different from the controls in the comparison of means by the individual and joint analyses. The less vigorous clones were statistically different from the others and from the controls, reflecting this difference in the genetic variability observed. The breeding program must consider the lack of difference between the most vigorous clones and the controls when recombining superior clones, since genetic gain depends on variability.